Determinants of demand for healthcare: a review of the literature - HOUMAM , Idriss; ADASKOU , Mohamed (Revue Internationale du Chercheur, 2023)
This work aims to describe the determinants of healthcare demand by exploiting a range of empirical studies. Indeed, the study and analysis of these factors are extremely important for formulating policies and strategies aimed at improving the conditions favoring the use and demand of healthcare and the health status of the population. The literature has reported a range of factors influencing the demand for and use of healthcare services. These determinants can be grouped into four categories: economic determinants (income, cost of care, insurance, ...), socio-demographic and cultural determinants (age, genre, professional status, family status, education level, origin, ethnicity, ...), disease-related determinants (severity of disease, previous health status, ...) and health care supply-related determinants (access to health care services, waiting time, quality of healthcare services, ...). In the majority of published studies, we can see that household characteristics, income, and the price of healthcare are the main determinants of the demand for healthcare.